Application of autogenic training in rehabilitation of patients with peptic ulcer of stomach and duodenum - Мелешков [Meleshkov V.], В'ячеслав Олександрович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Сonsiders the additional means of physical rehabilitation is psychotherapy. substantiates its use in the treatment of patients with peptic ulcer of stomach and duodenum. Great attention is focused on the elimination of psychological factors, as one of the causes of peptic ulcer. describes the conditions of, the method of autogenic training, and also lists the formula goal, used during meditating in the treatment and prevention of ulcers stomach and duodenal ulcer. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->